Allergen immunotherapy in China - Yang, Yaqi; Li, Wenjing; Zhu, Rongfei (Frontiers in Allergy, 2024)
Allergen immunotherapy (AIT) is an etiological treatment strategy that involves administering escalating doses of clinically relevant allergens to desensitize the immune system. It has shown encouraging results in reducing allergy symptoms and enhancing patients' quality of life. In this review, we offer a thorough overview of AIT in China, examining its efficacy, safety, current practices, and prospects. We further underscore the progress made in AIT research and clinical applications, as well as the distinct challenges and opportunities that China faces in this area.